THE STYLE AND THE METHOD OF THE WORKS OF FRANK NORRIS - Abdusattorova Nafisa Ikromitdin qizi (Journal of new century innovations, 2023)
Abstract: well- known American writer Frank Norris wrote a lot of brilliant novels during his lifetime. His works differ with his method which used in his novels. His notable works include McTeague: A Story of San Francisco, The Octopus: A story of California and The Pit. This article describes some features of Frank Norris as a writer and his works.